Effect of the Perceptions of Secondary School Teachers and Learners on the Implementation of Practical Skills for the Realization of Vision 2025 in Kilimanjaro Region, Tanzania - Kezia J. Mashingia; Joseph M. Malusu; Philip Kireti (Progress in Language, Literature and Education Research Vol. 7, 2024)
Vision 2025 recommends that education should lead to high-quality livelihood for all Tanzanians through strategies which ensure attainment of a level of tertiary education, hard work and creativity through implementation of practical skills among learners. Vision 2025 targeted subjects such as agriculture, business, ICT, together with STEM subjects namely science, technology, engineering and mathematics. Perceptions of teachers and learners on the implementation of practical skills for the realization of Vision 2025 among secondary school learners have not been documented in Kilimanjaro Region. Thus the aim of undertaking this study is to find out how these perceptions affect the implementation of practical skills for the realization of Vision 2025. This paper addresses one of the research questions which is: What are the perceptions of secondary school teachers and learners on the implementation of practical skills for the realization of Vision 2025 in Kilimanjaro Region, Tanzania? This study used convergent mixed methods design which is a concurrent design where qualitative data and quantitative data sets are collected together. The target population was 5278 people including DEOs, secondary school teachers, heads of schools, academic masters and Form four learners of government and secondary schools of three district councils. Probability and non-probability sampling were used. Data were collected through questionnaires, interview guide, document analysis schedules and observation schedules. The findings indicated positive perceptions of both teachers and learners towards the implementation of practical skills for the realization of Vision 2025. In conclusion, this implied that Vision 2025 could be realized through secondary education by learners acquiring practical skills which help them improve their livelihood. Both the secondary school teachers and learners perceived positively the implementation of practical skills for the realization of Vision 2025. The researcher recommended practical skills to be developed to A level, Tertiary and University levels. Further study could be done on the evaluation of the community’s perceptions towards developing practical skills among learners for the realization of Vision 2025.